Event‐based impulsive consensus for delayed multi‐agent systems. Issue 2 (22nd July 2021) - Wang, Yangling; Cao, Jinde; Wang, Haijun
Abstract: This paper focuses on the average consensus problem for delayed nonlinear multi‐agent systems. To reduce unnecessary energy consumption, a novel event‐triggered impulsive control mechanism is adopted, in which the impulsive time series is determined by some pre‐designed events. Simultaneously, the Zeno‐behavior of the event‐triggering time series is excluded. By using Lyapunov–Krasovskii functional method as well as impulsive control theory, an easy‐to‐check sufficient criterion is derived to ensure the average consensus of the considered nonlinear multi‐agent systems. Finally, the applications and effectiveness of the obtained results is validated with a simulation example.